PEMBERDAYAAN KELUARGA MELALUI PENDIDIKAN AGAMA - Suryadi Suryadi (ORASI: Jurnal Dakwah dan Komunikasi, 2016)
Globalization is the newest era when anything can't stop entering our environment, family and our children. Every value can colour our children. Through information technology cannal, Western Value can also enter our home. If the value that is enter in our home is positive, we can accept it. However, if the value is negative we have to push away it.  Anticipating the bad impact of negative value that will get in to our environment, the role of child aducation is not just in parents hands. It is a responsible any related-institutions i.e. School operating by teacher, Religious Leaders and etc. Further, any resposble people and institutions have to protect our children from bad impact of globalization by religious education. Parents and teachers in school have to demonstrate good example manner to their children and teach the good values of religious.Key words: globalization, education, children and youth